Efficiency in the UK Commercial Property Market: A Long-run Perspective - Steven Devaney; Oliver Holtemöller; Rainer Schulz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2012)
Informationally efficient prices are a necessary requirement for optimal resource allocation in the real estate market. Prices are informationally efficient if they reflect buildings' benefit to marginal buyers, thereby taking account of all available information on future market development. Prices that do not reflect available information may lead to over- or undersupply if developers react to these inefficient prices. In this study, we examine the efficiency of the UK commercial property market and the interaction between prices, construction costs, and new supply. We collated a unique data set covering the years 1920 onwards, which we employ in our study. First, we assess if real estate prices were in accordance with present values, thereby testing for informational efficiency. By comparing prices and estimated present values, we can measure informational inefficiency. Second, we assess if developers reacted correctly to price signals. Development (or the lack thereof) should be triggered by deviations between present values and cost; if prices do not reflect present values, then they should have no impact on development decisions. – – Informationseffiziente Preise sind eine Bedingung für die effiziente Allokation auf Immobilienmärkten. Preise auf Vermögensmärkten sind informationseffizient, wenn sie alle relevanten Informationen widerspiegeln und dem Fundamentalwert des Vermögensgutes entsprechen. Falls die Marktteilnehmer auf nicht informationseffiziente Preise reagieren, kann es zu einem Über- oder Unterangebot an Immobilien kommen, d. h. zu nicht effizienten Entscheidungen. In dieser Studie wird getestet, ob Preise für Gewerbeimmobilien in London im Zeitraum von 1920 bis 2008 als informationseffizient angesehen werden können und ob Immobilienentwickler systematisch auf Fehlbewertungen reagiert haben. Es wird gezeigt, dass es zwar Hinweise auf nicht effiziente Preisentwicklungen auf dem Londoner Gewerbeimmobilienmarkt gibt und dass die reale Bautätigkeit davon beeinflusst worden ist; die Effekte von Fehlbewertungen erklären aber nur einen relativ kleinen Anteil der Varianz der realen Bautätigkeit.
urn:nbn:de:101:1-201302046640
Keywords: C32; E30; G12; 330; asset pricing; bubbles; commercial property; London; real estate investment; Preisbildung auf Vermögensmärkten; Preisblasen auf Vermögensmärkten; Gewerbeimmobilien; London; Bauinvestitionen; Gewerbeimmobilien; Immobilienpreis; Informationseffizienz; Immobilienmarkt; Bauinvestition; Großbritannien; London